Multiomics-based analysis of the mechanism of ammonia reduction in Sphingomonas - Wang Mingcheng; Wang Mingcheng; Wang Mingcheng; Wang Mingcheng; Liu Daoqi; Xia Huili; Wang Gailing; Liu Chaoying; Guo Yanan; Guo Aizhen; Guo Aizhen; Guo Aizhen (Frontiers in Microbiology)
Ammonia is the primary component of malodorous substances in chicken farms. Currently, the microbial ammonia reduction is considered a potential method due to its low cost, high safety, and environmental friendliness. Sphingomonas sp. Z392 can significantly reduce the ammonia level in broiler coops. However, the mechanisms of ammonia nitrogen reduction by Sphingomonas sp. Z392 remain unclear. To explore the mechanisms of ammonia reduction by Sphingomonas sp. Z392, the transcriptome and metabolome analysis of Sphingomonas sp. Z392 under high ammonium sulfate level were conducted. It was found that the transcription levels of genes related to purine metabolism (RS01720, RS07605, purM, purC, purO) and arginine metabolism (glsA, argB, argD, aguA, aguB) were decreased under high ammonium sulfate environment, and the levels of intermediate products such as ornithine, arginine, IMP, and GMP also were also decreased. In addition, the ncd2 gene in nitrogen metabolism was upregulated, and intracellular nitrite content increased by 2.27 times than that without ammonium sulfate. These results suggested that under high ammonium sulfate level, the flux of purine and arginine metabolism pathways in Sphingomonas sp. Z392 might decrease, while the flux of nitrogen metabolism pathway might increase, resulting in increased nitrite content and NH3 release. To further verify the effect of the ncd2 gene on ammonia removal, ncd2 was successfully overexpressed and knocked out in Sphingomonas sp. Z392. ncd2 Overexpression exhibited the most ammonia reduction capability, the ammonia concentration of ncd2 overexpression group decreased by 43.33% than that of without Sphingomonas sp. group, and decreased by 14.17% than that of Sphingomonas sp. Z392 group. In conclusion, Sphingomonas sp. Z392 might reduce the release of NH3 by reducing the flux of purine and arginine metabolisms, while enhancing ammonia assimilation to form nitrite. In this context, ncd2 might be one of the key genes to reduce ammonia.